Description of Clean and Healthy Living Behavior (PHBS) With Hand Washing With Soap During The Covid-19 Pandemic in South Tangerang City in 2021 - Ghina Syania Zahirah; Hilda Mutiah; Klarysa Klarysa; Mutiara Ramadhani Putri; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The South Tangerang Health Office noted that there were 285 new cases of Covid 19 in April. The addition of positive cases in South Tangerang is the second-highest since the Covid-19 pandemic hit in March 2020. Based on several studies in the southern Tangerang city area, there is still a lack of knowledge, attitudes, and behavior in washing hands with soap. The purpose of this study was to determine the description of healthy and healthy behavior (PHBS) by washing hands with soap during the covid-19 pandemic in the city of South Tangerang. The type of research used is qualitative research. The statements of the four informants regarding their knowledge, attitudes, and behavior regarding handwashing with soap during this pandemic are quite good. Washing hands with soap during this pandemic is very important. According to the results of research on members of each researcher in South Tangerang City, washing hands with soap during the pandemic has considered very important.